Legal Consequences of State Administrative Decisions That Violate Good Governance: An Analysis of Islamic Law and Positive Law on the SDGs - Ahmad Rosidi; Awaludin; I Made Suradana; Obydur Rahman (Profetika: Jurnal Studi Islam, 2025)
Objective: This study examines the legal consequences of State Administrative Decisions that violate the General Principles of Good Governance (Asas-Asas Umum Pemerintahan yang Baik/AUPB) as regulated in Law Number 30 of 2014 on State Administration, analyzed through the perspectives of Islamic law, positive law, and the Sustainable Development Goals (SDGs). Theoretical framework: The theoretical framework is grounded in the rule of law and good governance theory, emphasizing legality, accountability, and justice in public administration. This framework is complemented by Islamic legal principles such as amanah (trust), ‘adl (justice), and responsibility of rulers, which reinforce ethical governance. From an SDGs perspective, the study aligns particularly with SDG 16, which promotes effective, accountable, and transparent institutions. Literature review: The literature review covers doctrines of administrative law, principles of good governance, Law Number 30 of 2014, and classical as well as contemporary Islamic legal thought concerning justice, leadership ethics, and accountability. Methods: This research employs a normative juridical method through library-based legal research. Data sources include primary legal materials such as statutes and state administrative decisions, secondary materials including scholarly books and journal articles, and tertiary materials such as legal dictionaries and encyclopedias. Qualitative legal analysis is used to interpret norms and evaluate their coherence. Results: The findings indicate that State Administrative Decisions involving dishonesty, abuse of authority, conflicts of interest, or regulatory violations constitute maladministration and weaken democratic governance. From an Islamic law perspective, such decisions violate core ethical principles, while from a positive law perspective, they trigger legal responsibility and administrative sanctions. Implications: The implications emphasize the urgency of strengthening AUPB enforcement, harmonizing Islamic legal values with democratic governance, and enhancing oversight mechanisms to prevent KKN practices. Novelty: The novelty of this study lies in its integrative analysis that bridges state administrative law, Islamic legal ethics, democratic theory, and SDGs-oriented governance.